Maintenance DNA methyltransferase activity in the presence of oxidized forms of 5-methylcytosine: structural basis for ten eleven translocation-mediated DNA demethylation - Seiler, Christopher L. (Biochemistry, 2018)
A precise balance of DNA methylation and demethylation is required for epigenetic control of cell identity, development, and growth. DNA methylation marks are introduced by de novo DNA methyltransferases DNMT3a/b and are maintained throughout cell divisions by DNA methyltransferase 1 (DNMT1), which adds methyl groups to hemimethylated CpG dinucleotides generated during DNA replication. Ten Eleven Translocation (TET) dioxygenases oxidize 5-methylcytosine (mC) to 5-hydroxymethylcytosine (hmC), 5-formylcytosine (fC), and 5-carboxylcytosine (caC), a process known to induce DNA demethylation and gene reactivation. In the present study, we investigated the catalytic activity of human DNMT1 in the presence of oxidized forms of mC. A mass spectrometry-based assay was employed to study the kinetics of DNMT1-mediated cytosine methylation in CG dinucleotides containing C, mC, hmC, fC, or caC across from the target cytosine. Homology modeling, coupled with molecular dynamics simulations, was carried out to explore the structural consequences of mC oxidation in regard to the geometry of protein-DNA complexes. DNMT1 enzymatic activity was strongly affected by the oxidation status of mC, with catalytic efficiency decreasing in the order mC > hmC > fC > caC. Molecular dynamics simulations revealed that DNMT1 forms an unproductive complex with DNA duplexes containing oxidized forms of mC as a consequence of altered interactions of the target recognition domain of the protein with the C-5 substituent on cytosine. Our results provide a new structural and mechanistic insight into TET mediated DNA demethylation.